Electrochemical extraction of cemented carbide
The extraction of metal from cemented carbide substrates through electrochemical methods of non-aqueous solvents solves the problems of unenvironmental and high cost in the existing recycling methods, and achieves high-quality output and low environmental impact metal recycling effects.
Patent Information
- Application Number
- CN202410912239.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-07-10
- Filing Date
- 2024-07-09
- Publication Date
- 2025-01-10
AI Technical Summary
Existing cermet and carbide recycling methods are not environmentally friendly and costly, making it difficult to achieve high-quality output and low environmental impact.
The metal is extracted from the cemented carbide substrate by electrochemical method using a non-aqueous solvent. By immersing the cemented carbide substrate as an anode and applying current to the cathode, the electrochemical extraction and recovery of the metal is achieved.
High-quality metal extraction is achieved, reducing environmental impact and energy efficiency, and providing an environmentally friendly and cost-saving metal recycling method.
Smart Images

Figure CN119287448A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to metal extraction from cemented carbides, and more particularly to electrochemical metal extraction. Background Art
[0002] Metal-based cermets or cemented carbides have high wear resistance, high hardness, high melting point and excellent corrosion resistance. Therefore, they are used in a wide range of applications, including machine tool manufacturing, military ammunition and aerospace, etc. The widespread use of metal-based cermets or cemented carbides generates a large amount of alloy waste. Different processes have been developed to recover the metals contained in cermets and cemented carbides, including hydrometallurgy and powder metallurgy. However, these methods are not environmentally friendly and are not cost-effective. It is desirable to have an extraction method that achieves high-quality output while having less environmental impact and higher energy efficiency. Summary of the invention
[0003] The present invention provides an electrochemical method for extracting metal from a cemented carbide substrate using a non-aqueous solvent. The method comprises immersing a substrate comprising a cemented carbide, the cemented carbide comprising a metal carbide and a metal, in an electrolyte comprising a non-aqueous solvent, wherein the substrate serves as an anode; immersing a cathode in the electrolyte; applying an electric current between the substrate and the cathode, thereby extracting the metal from the substrate; and recovering the extracted metal. BRIEF DESCRIPTION OF THE DRAWINGS
[0004] Figure 1 The extraction method is schematically illustrated.
[0005] Figure 2 A sample of the prepared electrode is shown.
[0006] Figure 3 A system for carrying out the extraction method is schematically illustrated.
[0007] Figure 4A The concentration of Co extracted during electrodissolution performed at 4 V is shown as a function of temperature.
[0008] Figure 4B The concentration of Ni extracted during electrodissolution performed at 4 V is shown as a function of temperature.
[0009] Figure 4C The concentration of W extracted during electrodissolution performed at 4 V is shown as a function of temperature.
[0010] Figure 4D The concentration of extracted Fe during electrodissolution performed at 4 V is shown as a function of temperature.
[0011] Figure 5A The concentration of Co extracted during electrodissolution performed at 60°C is shown as a function of voltage.
[0012] Figure 5B The concentration of Ni extracted during electrodissolution performed at 60°C is shown as a function of voltage.
[0013] Figure 5C The concentration of W extracted during electrodissolution performed at 60°C is shown as a function of voltage.
[0014] Figure 5D The concentration of extracted Fe during electrodissolution performed at 60°C is shown as a function of voltage.
[0015] Fig. 6A A SEM image of the surface of a bare stainless steel electrode is shown.
[0016] Figure 6B Shown is a SEM image of the surface of the stainless steel electrode of Example 4 after exposure to a current of 4 V at 80°C.
[0017] Figure 6C Shown is a SEM image of the surface of the stainless steel electrode of Example 4 after exposure to a current of 4 V at 25°C.
[0018] Fig.6D Shown is a SEM image of the surface of the stainless steel electrode of Example 4 after exposure to a current of 2 V at 60°C.
[0019] Fig. 6E Shown is a SEM image of the surface of the stainless steel electrode of Example 4 after exposure to a current of 4 V at 40°C.
[0020] Fig. 6F Shown is a SEM image of the surface of the stainless steel electrode of Example 4 after exposure to a current of 6 V at 60°C.
[0021] Figure 6G Shown is a SEM image of the surface of the stainless steel electrode of Example 4 after exposure to a current of 4 V at 60°C.
[0022] Figure 6H An image of the surface of the stainless steel electrode of Example 4 after exposure to a current of 8 V at 60°C is shown.
[0023] Figure 7 Shown are X-ray diffraction patterns of electrodes deposited at different temperatures.
[0024] Figure 8 X-ray diffraction patterns of electrodes deposited at different voltages are shown.
[0025] Fig. 9A Shown are optical surface measurements of the SS electrode after deposition.
[0026] Fig. 9BOptical surface measurements of the SS / AC electrodes after deposition are shown.
[0027] Fig. 9C Shown are optical surface measurements of the SS / AC / PANI electrode after deposition.
[0028] Fig. 10A Shown is a SEM image of the SS electrode before deposition.
[0029] Fig. 10B Shown is the SEM image of the SS electrode after deposition.
[0030] Fig. 10C Shown is a SEM image of the SS / AC electrode before deposition.
[0031] Fig. 10D Shown is a SEM image of the SS / AC electrode after deposition.
[0032] Fig.10E Shown is a SEM image of the SS / AC / PANI electrode before deposition.
[0033] Fig.10F Shown is the SEM image of the SS / AC / PANI electrode after deposition.
[0034] Fig.11A is a graph showing the extraction rate of Co as a function of time during electrodissolution at 4 V and 25° C. using a SS electrode, a SS / AC electrode, and a SS / AC / PANI electrode.
[0035] Fig. 11B is a graph showing the extraction rate of Ni as a function of time during electrodissolution at 4 V and 25° C. using a SS electrode, a SS / AC electrode, and a SS / AC / PANI electrode.
[0036] Fig. 11C is a graph showing the extraction rate of W as a function of time during electrodissolution at 4 V and 25° C. using a SS electrode, a SS / AC electrode, and a SS / AC / PANI electrode.
[0037] Fig.11D is a graph showing the extraction rate of Fe as a function of time during electrodissolution at 4 V and 25° C. using a SS electrode, a SS / AC electrode, and a SS / AC / PANI electrode.
[0038] Fig.12 XRD analysis of the surfaces of the SS-deposited electrode, the SS / AC-deposited electrode, and the SS / AC / PANI-deposited electrode are shown. DETAILED DESCRIPTION
[0039] Figure 1A system for performing electrochemical extraction of metals and / or carbides is schematically illustrated. The system comprises an electrochemical cell 10 comprising an anode 12 comprising a prefabricated cemented carbide scrap substrate containing metal carbides and a binder metal and a cathode 14 immersed in a bath of an electrolyte 18 containing an ionic solvent. The anode 12 and cathode 14 are connected to a regulated DC power supply 15. The electrolyte 18 is separated by a porous membrane or separator 16.
[0040] like Figure 1 As further shown, during the electrochemical process, the electrolytic cell 10A is operated by providing an electric current from a DC power source 15 through an electrolyte 18 to a submerged anode 12 and a submerged cathode 14. When the electric current is applied, the metal carbide 20 and the binder metal 30 contained in the anode 12 are electrochemically loaded into the electrolyte 18. The metal carbide 20 is insoluble in the electrolyte 18 and precipitates out of the electrolyte 18. The binder metal that is soluble in the electrolyte 18 passes through the porous membrane separator 16, where a portion of it can be deposited 32 onto the surface of the cathode 14. In addition to such deposits 32, some or all of the metal can be dissolved into the electrolyte in the form of dissolved metal 30. During operation, the electrolyte can be stirred and heated to control the temperature of the electrolyte 18.
[0041] The ionic solvent of the electrolyte 18 is then delivered 42 to a solvent extraction system where it is mixed with a second solvent, such as octan-1-ol, for solvent extraction of the binder metal. The metal carbides 20 are extracted from the ionic solvent by filtration and then washed and dried for reuse. The ionic solvent is then recycled back into the electrolyte 18 after the metal is extracted.
[0042] Figure 1 The system shown in can be provided as a closed loop system. As used herein, "closed loop system" refers to a system in which the electrolytic cell and the solvent extraction process are fluidly connected, such as by a piping system, thereby allowing the system to operate continuously without the need for a separate step of recovering the electrolyte and metal for solvent extraction.
[0043] During the electrochemical extraction method disclosed herein, a substrate comprising a cemented carbide is used as an anode 12. Anode 12 and cathode 14 are immersed in an electrolyte 18 comprising a non-aqueous solvent. As used herein, the term "non-aqueous solvent" means a solvent that is substantially free of water, for example, meaning that water is not present, or is present only in a minimal amount as an impurity, rather than being purposefully added to the solvent. The non-aqueous solvent may include an ionic solvent, be substantially composed of an ionic solvent, or be composed of an ionic solvent. As used herein, "ionic solvent" refers to a solvent comprising an anionic component and a cationic component. The ionic solvent may include a eutectic solvent. As used herein, "eutectic solvent" refers to a solvent comprising a first compound containing a hydrogen bond acceptor and a second compound containing a hydrogen bond donor, wherein the melting point of the eutectic solvent is lower than the melting point of the first compound alone and the melting point of the second compound alone. The eutectic solvent may include a deep eutectic solvent. As used herein, "deep eutectic solvent" or "DES" refers to a eutectic solvent that exhibits a melting point significantly lower than the first compound and the second compound, for example at least 100°C lower, or at least 200°C lower, or at least 300°C lower, or at least 400°C lower.
[0044] Any suitable hydrogen bond acceptor known in the art may be used. Examples of suitable hydrogen bond acceptors include, but are not limited to, compounds containing phosphonium cations and / or ammonium cations, including quaternary ammonium cations and / or non-quaternary ammonium cations. Suitable compounds containing quaternary ammonium cations include, for example, choline chloride ([(CH3)3NCH2CH2OH] + Cl - ), tetra-n-butylammonium bromide, tetra-n-ethylammonium chloride and tetramethylammonium chloride. Suitable compounds containing non-quaternary ammonium cations include, for example, 2-(chlorocarbonyloxy)-N,N,N-trimethylethylammonium chloride, N-benzyl-2-hydroxy-N,N-dimethylethylammonium, N,N-diethylethanolammonium chloride and N-ethyl-2-hydroxy-N,N-dimethylethylammonium chloride. Suitable compounds containing phosphonium cations include, for example, benzyltriphenylphosphonium chloride and methyltriphenylphosphonium bromide. Other suitable hydrogen bond acceptors include, but are not limited to, lidocaine; amino acids including alanine, glycine, proline and histidine; nicotinic acid; choline fluoride; and betaine.
[0045] Any suitable hydrogen bond donor known in the art can be used. Hydrogen bond donors can include, for example, glycerol (C3H8O3), ethylene glycol, urea, adipic acid, acetamide, phenol, benzamide, benzoic acid, thymol, malonic acid, thiourea, succinic acid, 1,3-dimethylurea, oxalic acid, lactic acid, citric acid, 1-methylurea, 1-naphthol, glucose, 1,1-dimethylurea, 1,4-butanediol, decanoic acid, fructose, triethylene glycol, dodecanoic acid, methanol, or a combination thereof.
[0046] The hydrogen bond acceptor and the hydrogen bond donor may be present in a molar ratio of at least 1:4, such as at least 3:7. The hydrogen bond acceptor and the hydrogen bond donor may be present in a molar ratio of no more than 2:3, such as no more than 1:2. The hydrogen bond acceptor and the hydrogen bond donor may be present in a molar ratio of 1:4 to 2:3, such as 3:7 to 1:2. In an example, the hydrogen bond acceptor and the hydrogen bond donor may be present in a molar ratio of 1:2.
[0047] Suitable substrates that can be used in the present invention are any substrates that contain cemented carbide. The substrate may contain hard scrap and / or soft scrap of cemented carbide. As used herein, the term "hard scrap" refers to the final product prepared from cemented carbide. As used herein, the term "soft scrap" refers to the sludge, debris and / or other waste formed in the process of forming a product containing cemented carbide. It has been surprisingly found that the method disclosed herein can be used to extract metals from soft scrap. However, any cemented carbide substrate can be used in the method disclosed herein. The extraction method disclosed herein is superior to conventional methods, such as acid leaching that can chemically modify the extracted metal.
[0048] The cemented carbide may comprise, consist essentially of, or consist of a metal carbide and a metal binder.
[0049] The metal carbide may include a Group IVB metal carbide, a Group VB metal carbide, a Group VIB metal carbide, or a combination thereof. For example, the metal carbide may include tungsten carbide, chromium carbide, titanium carbide, vanadium carbide, tantalum carbide, niobium carbide, zirconium carbide, and / or hafnium carbide. For example, the metal carbide may include tungsten carbide.
[0050] The metal binder or metal of the cemented carbide may include cobalt, cobalt alloy, nickel, nickel alloy, iron, iron alloy or a combination thereof. In some embodiments, the metal binder may include cobalt and / or cobalt alloy. The metal binder may include one or more additives, such as a noble metal additive. Examples of noble metal additives that may be used in cemented carbide include, but are not limited to, platinum, palladium, rhenium, rhodium and ruthenium and alloys thereof. Other additives include molybdenum, silicon or a combination thereof.
[0051] The cathode is also immersed in the electrolyte. The cathode may include any conductive material known in the art, such as conductive metals and their alloys. Suitable conductive materials include, but are not limited to, titanium, aluminum, iron, copper and their alloys. The metal or metal alloy may include or be steel, such as stainless steel, cold rolled steel, hot rolled steel, electrogalvanized steel and / or hot dip galvanized steel. The cathode may include a coating comprising activated carbon on at least a portion of the surface of the cathode. Surprisingly, it was found that a cathode comprising stainless steel coated with activated carbon significantly improved the efficiency of extracting metal from a cemented carbide substrate when compared to a bare stainless steel cathode.
[0052] The current and temperature at which the electrochemical extraction process is performed can be adjusted in order to achieve the desired effect. Higher voltages and temperatures result in more efficient extraction of metal from cemented carbide. Lower voltages and temperatures result in more uniform deposition and selective deposition of metal on the surface of the cathode.
[0053] During electrochemical extraction, current is applied to the anode and cathode. The current can be at least 1V, such as at least 2V, such as at least 3V, such as at least 4V. The current can be no more than 10V, such as no more than 8V, such as no more than 7V, such as no more than 6V. The current can be 1V to 10V, such as 2V to 8V, such as 3V to 7V, such as 4V to 6V.
[0054] During electrochemical extraction, the electrolyte may be heated to a temperature of at least 20° C., such as at least 25° C., such as at least 30° C., such as at least 40° C. The electrolyte may be heated to a temperature of no more than 100° C., such as no more than 90° C., such as no more than 80° C., such as no more than 60° C. The electrolyte may be heated to a temperature of 20° C. to 100° C., such as 25° C. to 90° C., such as 30° C. to 80° C., such as 40° C. to 60° C.
[0055] When an electric current is applied to the anode and cathode, at least one metal is extracted from the substrate comprising the cemented carbide. The extracted metal may be soluble, such as nickel, cobalt, iron, or a combination thereof. The metal carbide is separated from the substrate and is insoluble in ionic solvents.
[0056] The extracted metal may be deposited onto a portion of the surface of the cathode. For example, cobalt may be deposited onto the cathode. Soluble metals may be deposited onto the surface of the cathode in elemental form.
[0057] After applying the electric current, the extracted metal is recovered from the non-aqueous solvent. The metal can be extracted by any method known in the art. For example, insoluble metals can be recovered by filtration. In other examples, soluble metals can be recovered by standard solvent extraction methods.
[0058] The following examples are intended to illustrate various aspects of the present invention but are not intended to limit the scope of the present invention.
[0059] Example
[0060] Example 1: Preparation of soft cemented carbide scrap
[0061] Cemented carbide soft scrap samples were prepared by drying in an oven at 110°C for 2 hours to remove any moisture contamination. The elemental composition of the soft scrap samples was analyzed using an Olympus Vanta C Series XRF and the results are provided in Table 1. The soft 9 scrap samples were weighed and bagged using cotton cloth.
[0062] Table 1
[0063] Element composition of carbide lathe chips
[0064]
[0065]
[0066] Example 2: Preparation of electrolyte
[0067] A deep eutectic solvent (DES) was prepared using choline chloride (ChCl) and glycerol (analytical grade) in a molar ratio of ChCl:glycerol of 1:2. ChCl and glycerol were mixed at 80°C in a vacuum / nitrogen atmosphere. The solution was stirred continuously until a consistent clear liquid was obtained. Before use, it was further dried at 110°C under vacuum for 24 hours to remove any moisture.
[0068] Example 3: Preparation of electrodes
[0069] Three S316 grade stainless steel (SS) plates with a thickness of 0.25 mm were cut into a size of 1 cm x 1 cm. Various grades of diamond abrasive sheets were used to polish the surfaces of the samples by applying force unidirectionally through a standard polishing procedure. After polishing, the surfaces were rinsed with distilled water and acetone.
[0070] The electrode slurry was prepared by mixing 50 mg of activated carbon (Enasco 350G, Imerys Graphite and Carbon) and 1% of polyvinylidene fluoride (PVDF) (Sigma-Aldrich) in N-methyl-2-pyrrolidone to produce a homogeneous slurry.
[0071] The electrode slurry was coated on the surfaces of the two SS plates with a thickness of 0.04 mm using a manual doctor blade method. The activated carbon-coated stainless steel plates (SS / AC) were dried in an oven at 50° C. for 12 hours.
[0072] One SS / AC plate was used for electrochemical polymerization of 0.1N sulfuric acid, 0.1M sodium dodecyl sulfate (SDS), and 0.1M aniline containing aniline to form a new SS / AC / PANI plate. The electropolymerization of polyaniline (PANI) containing aniline on the sample was performed by cyclic voltammetry (CV) in a potential window of 0.2V to 0.8V at 10mV / s using a Gamry reference 600+ potentiostat / galvanostat controlled by the framework software using a three-electrode system. A saturated calomel electrode (SEC) was used as a reference, and a platinum electrode was used as a counter electrode for 20 CV cycles to obtain PANI grafting on the sample electrode. Figure 2An image of the sample electrodes is provided in . The left electrode contains SS, the middle electrode contains SS / AC, and the right electrode contains SS / AC / PANI.
[0073] The extraction efficiencies of the SS electrode plate, SS / AC electrode plate, and SS / AC / PANI electrode plate were compared, followed by metal deposition and characterization.
[0074] Example 4: Electrochemical Experiment
[0075] like Figure 3 As schematically shown in FIG. 1 , an anode 12 comprising a soft waste sample and a cathode 14 comprising stainless steel are immersed in a DES electrolyte 18 for 4 hours. Figure 3 As shown in . A porous membrane separator 16 is placed in the electrolyte between the anode 12 and the cathode 14. Aplan L3205 regulated DC power supply device 15 is used to provide current to the system. The electrolyte is heated by a heating mechanism 19. The voltage and temperature vary with the experimental conditions. The results are provided in Table 2. Electrolyte samples (E1, E2, E3, E4 and E5) were collected every hour during the four hours and analyzed for the presence of cobalt, tungsten, nickel and iron using a Perkin Elmer Optima 8000 inductively coupled plasma-optical emission spectrometer (ICP-OES). As Figures 4A-4D As shown in , the loading of Co, Ni, W, and Fe in the electrolyte is higher when the electrodissolution is performed at about 60 °C. Figures 5A-5D As shown in , when the electrodissolution process is performed at about 8 V, the loading amounts of Co, Ni, W, and Fe in the electrolyte are higher.
[0076] The stainless steel electrodes were also analyzed using scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDS) and X-ray diffraction (XRD). Figures 6A-6H SEM images of the electrode surface at different temperatures and voltages are provided in . As shown, changes in the temperature and voltage at which electrodissolution occurs result in differences in deposition thickness, uniformity, and flake size. As the temperature increases from room temperature (25°C) to 80°C, deposition increases, but the uniformity of the deposit size decreases. As the voltage increases from 2V to 8V, the flatness of the deposit decreases, and the uniformity of the deposit size increases. In Figure 7 and 8 The X-ray diffraction patterns of the deposited electrodes for different temperatures and voltages are provided in Figure 2. The deposition increases as the temperature increases from 25°C to 80°C at a constant voltage of 4 V. The deposition also increases as the voltage increases from 2V to 8V at a constant temperature of 60°C.
[0077] Example 5: Modified Electrode Characterization
[0078] like Figures 9A-9CAs shown in, the surface morphology and roughness of the deposits on the modified electrode were plotted using a Bruker alicona G5 optical surface measurement system to visualize the properties and consistency of the deposits. The electrodes comprising SS and SS / AC / PANI showed uniform electrode surface roughness after deposition, indicating uniform deposition. The electrodes comprising SS / AC showed surface roughness variation, indicating uneven surface deposition.
[0079] SEM analysis as previously disclosed herein was also performed on the modified electrodes. Figures 10A-10F SEM images of the electrodes before and after deposition are provided in . The deposit on the SS electrode was found to be a uniform rough surface layer with fine microcracks. The deposit on the SS / AC electrode was found to be spherical and fluffy with a uniform diameter of less than 1 micron. The surface morphology of the deposit was found to uniformly cover the activated carbon surface with good adhesion due to the fluffy surface of the spheres. The deposit on the SS / AC / PANI electrode was found to be granular in nature with multiple particles welded to form clusters of deposits with diameters ranging from 0.5 microns to less than 10 microns. Due to the weld-like structure, the deposit was uniform over the entire surface with good adhesion.
[0080] Figures 11A-11D The extraction rates of various modified electrodes for Co, Ni, W, and Fe at 4 V and 25 °C are provided. As shown, the SS / AC electrode has significantly higher extraction rates for cobalt, nickel, and tungsten relative to the SS and SS / AC / PANI electrodes. The SS / AC electrode has a significantly higher extraction rate for iron than the SS electrode. Fig.12 XRD analysis of the modified electrodes is provided. As shown, the SS / AC deposited electrodes have sharper peaks, which indicates the high crystallinity of these cobalt deposits on the electrode surface. It was surprisingly found that the modified electrodes helped to change the surface morphology and deposition rate due to the increased surface area of the electrode.
[0081] Table 2
[0082] Electrodissolution Experiment Details
[0083]
[0084]
[0085] For the purpose of this specific embodiment, it should be understood that the present invention can adopt various alternatives and step sequences, unless explicitly stated to the contrary. In addition, except in any operating examples, or where otherwise specified, all numbers used in the specification and claims to indicate, for example, the amount of ingredients should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the following specification and the attached claims are approximate values, which can vary according to the desired characteristics obtained by the present invention. At a minimum, and without attempting to limit the application of the doctrine of equivalents to the scope of the claims, each numerical parameter should at least be interpreted in accordance with the number of reported significant digits and by applying ordinary rounding techniques.
[0086] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.
[0087] Likewise, it should be understood that any numerical range recited herein is intended to include all sub-ranges contained therein. For example, the range "1 to 10" is intended to include all sub-ranges between the recited minimum value of 1 and the recited maximum value of 10 (and including the minimum and maximum values), i.e., having a minimum value equal to or greater than 1 and a maximum value equal to or less than 10.
[0088] As used herein, "comprising," "containing," and similar terms are understood in the context of this application to be synonymous with "comprising," and are therefore open-ended and do not exclude the presence of additional undescribed or unlisted elements, materials, components, or method steps. As used herein, "consisting of" is understood in the context of this application to exclude the presence of any unspecified elements, ingredients, or method steps. As used herein, "consisting essentially of" is understood in the context of this application to include the specified elements, materials, ingredients, or method steps "as well as those elements, materials, ingredients, or method steps that do not materially affect the basic and novel characteristics described."
[0089] In this application, unless specifically stated otherwise, the use of the singular includes the plural and the plural encompasses the singular. For example, although reference is made herein to "a" substrate, "a" non-aqueous solvent, and "an" electrolyte, combinations (ie, multiples) of these components may be used.
[0090] Additionally, in this application, unless explicitly stated otherwise, the use of "or" means "and / or" even though "and / or" may be explicitly used in certain circumstances.
[0091] Although specific aspects of the present invention have been described in detail, it will be appreciated by those skilled in the art that various modifications and substitutions may be made to these details in light of the overall teachings of the present disclosure. Therefore, the specific arrangements disclosed are intended to be illustrative only and not limiting of the scope of the present invention, which is given by the full scope of the appended claims and any and all equivalents thereof.
Claims
1. A method for electrochemically extracting metal from cemented carbide, the method comprising: immersing a substrate comprising a cemented carbide comprising a metal carbide and a metal in an electrolyte comprising a non-aqueous solvent, wherein the substrate serves as an anode; immersing a cathode in the electrolyte; applying an electric current between the substrate and the cathode, thereby extracting the metal from the substrate; as well as The extracted metals are recovered.
2. The method of claim 1, wherein the metal is capable of being dissolved in the electrolyte and recovered by solvent extraction.
3. The method of claim 1, wherein the metal is deposited onto the cathode.
4. The method of claim 1, wherein the metal comprises cobalt, nickel, iron, combinations thereof, or alloys thereof.
5. The method of claim 1, wherein the metal comprises cobalt.
6. The method of claim 1, wherein the metal carbide is removed from the substrate.
7. The method of claim 1, wherein the metal carbide is insoluble in the electrolyte.
8. The method of claim 1, further comprising recovering the metal carbide.
9. The method of claim 8, wherein the metal carbide comprises tungsten carbide, chromium carbide, titanium carbide, vanadium carbide, tantalum carbide, niobium carbide, zirconium carbide, or combinations thereof.
10. The method of claim 8, wherein the metal carbide comprises tungsten carbide.
11. The method of claim 8, wherein said recovering of said metal carbides comprises filtering said electrolyte.
12. The method of claim 1, wherein the non-aqueous solvent comprises an ionic solvent.
13. The method of claim 12, wherein the ionic solvent comprises a first compound comprising a hydrogen bond acceptor and a second compound comprising a hydrogen bond donor.
14. The method of claim 9, wherein the ionic solvent comprises a eutectic solvent, wherein the eutectic solvent exhibits a melting point lower than a melting point of the first compound alone and a melting point of the second compound alone.
15. The method of claim 14, wherein the eutectic solvent comprises a deep eutectic solvent, wherein the deep eutectic solvent exhibits a melting point at least 100°C lower than the melting point of the first compound alone and the melting point of the second compound alone.
16. The method of claim 13, wherein the hydrogen bond acceptor comprises choline chloride and the hydrogen bond donor comprises ethylene glycol.
17. The method of claim 16, wherein the hydrogen bond acceptor and the hydrogen bond donor are present in a molar ratio of at least 1:
4.
18. The method of claim 1, wherein the cathode comprises stainless steel.
19. The method of claim 1, wherein the cathode comprises a coating comprising activated carbon on at least a portion of a surface of the cathode.
20. The method of claim 1, wherein the current is 1V to 10V.
21. The method of claim 1, wherein the electrolyte is maintained at a temperature of 20°C to 100°C.
22. The method of claim 1, wherein the electrolyte is provided in a bath, at least a portion of the electrolyte and the metal are removed from the bath, and after the metal is extracted from the electrolyte, at least a portion of the electrolyte is recycled to the bath.
23. The method of claim 1, wherein the method is performed in a closed loop system.
24. The method of claim 22, further comprising recovering the metal carbide from the electrolyte.
Citation Information
Cited By
Method for extracting gold resources in urban mineral products based on TEMPO electro-catalysis-histidine gold leaching agent system
CN120193163A